2006
DOI: 10.1086/501116
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosynthesis in the Outflow from Gamma‐Ray Burst Accretion Disks

Abstract: We examine the nucleosynthesis products that are produced in the outflow from rapidly accreting disks. We find that the type of element synthesis varies dramatically with the degree of neutrino trapping in the disk and therefore the accretion rate of the disk. Disks with relatively high accretion rates such asṀ ¼ 10 M s À1 can produce very neutron-rich nuclei that are found in the r-process. Disks with more moderate accretion rates can produce copious amounts of nickel, as well as the light elements such as li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(209 citation statements)
references
References 50 publications
(58 reference statements)
6
201
0
1
Order By: Relevance
“…We draw the same conclusions regarding 56 Ni production when we repeat the nucleosynthesis calculations using the outflow model from [18].…”
Section: Element Synthesissupporting
confidence: 65%
See 1 more Smart Citation
“…We draw the same conclusions regarding 56 Ni production when we repeat the nucleosynthesis calculations using the outflow model from [18].…”
Section: Element Synthesissupporting
confidence: 65%
“…Element synthesis in the hot outflows from merger-type black hole accretion disks has previously been addressed in, e.g., [17,18,19,20,21,22]. These found neutron-rich outflows to be possible in this environment, and thus suggested that merger-type disk winds may be an important source of particularly the lighter r-process nuclei.…”
Section: Introductionmentioning
confidence: 91%
“…For the role of weak interactions and resulting nucleosynthesis see e.g. [25,69,70]). The basic (consensus) picture is the following: explosion energies can be found up to 5 × 10 52 erg, 56 Ni ejecta up to 0.5 M ⊙ , and the ejecta are beamed with relativistic jets.…”
Section: Long Duration Gamma-ray Bursts and Hypernovaementioning
confidence: 99%
“…Black hole accretion disks are the final stage of neutron star mergers and can also provide the lower mass r-process elements [27,82]. They will also occur for the collapse of massive stars resulting in lGRBs/Hypernovae, but are not expected to produce heavy r-elements (unless special neutrino properties permit so, [69]). But these clearly produce large amounts of Ni/Fe which would be in contradiction with the non-correlation of r-process elements with Fe/Ni.…”
Section: Observational Constraintsmentioning
confidence: 99%
“…Using the typical conditions in neutrino-driven winds from PNSs for comparison, we can identify promising r-process scenarios involving other types of CCSN ejecta based on whether they have lower Y e , higher S 0 , shorter τ dyn , or any combination of the above. Lower Y e can be obtained in winds from accretion disks (or tori) surrounding black holes that are formed in special CCSNe associated with long gamma-ray bursts [57,58] or in neutron star mergers associated with short ones [59,60]. The dense disk material is neutron rich due to electron capture and emits ν e with a harder spectrum than that of ν e .…”
Section: Other Scenarios Involving Ccsn Ejectamentioning
confidence: 99%